Penggunaan Retorika Ayub 2:9-10 Dan Implikasinya Terhadap Keharmonisan Rumah Tangga Masa Kini - Wulansari, Elok Kartika; Zendrato, Petrus (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2025)
In Job 2:9-10 there is the use of rhetoric through Job's answer to his wife in understanding God's will through reality and the firmness in maintaining faith through the process. This article aims to apply the use of rhetoric in Job 2:9-10 and its implications for today's household harmony. In the literature review, there is a gap in previous research in discussing this rhetorical context of Job's response. Based on the qualitative method in the literature approach, this study found several things, namely: first, that the use of the rhetoric of Job 2:9 is a wise thing to be able to maintain harmony in today's households, and the rhetoric of Job 2:10 is Job's assertiveness in declaring his faith before his wife; second, the implications that can be applied to today's household harmony, especially for believers' households, are: (1). Husband and wife must live in fear of God; (2). Husband and wife must love one another; (3). Husbands and wives must be faithful; (4). Wives are to submit to their husbands; and (5). Husbands are to be firm against sin in the family.